Responsibilities of Online Teachers and On-Site Facilitators in Online High School Courses. Issue 1 (2nd January 2019) - Borup, Jered; Stimson, Rebecca J.
ABSTRACT: Local schools are increasingly providing their students who are enrolled in an online course with an on-site facilitator as a means for increasing online pass rates. However, few studies have examined how online teachers and on-site facilitators work in conjunction to support online students. Successful on-site facilitators ( n = 12) and online teachers ( n = 12) participated in two one-hour interviews. Analysis found that while both the teachers and the facilitators assumed extensive and complex roles, their responsibilities were overlapping but complementary. Although the facilitators were highly engaged in supporting students, online teachers found the quality of support provided by facilitators varied greatly across schools. Eleven of the facilitators required the majority of their students to attend a daily lab that allowed them more easily and effectively fulfill their responsibilities. Findings from this research also support the need to provide facilitators with professional development so that they can better assume their critical responsibilities.